Assessment of Anti-Lithiatic Activity in Pedalium murex L as A Binding Agent in Calcium Oxalate and Magnesium Trisilicate Tablets - G, Geetha.; M, Ranjithkumar.; A, Sarathi.; raj. P, Thendral (Journal of Neonatal Surgery, 2025)
One of the oldest diseases that humans have ever encountered is renal lithiasis, which was first recorded in ancient Greek. Renal lithiasis is the result of a change in the typical crystallization conditions of urine in the urinary system. Kidney stones are frequently caused by calcium, phosphate, and oxalate. Developing an oral herbal dose formulation of Pedalium murex L as a binding agent in calcium oxalate and magnesium trisilicate tablets with assessed anti-urolithiatic activity was the main goal of this investigation. Phytochemical screenings of Pedalium murex L leaf extracts showed presence of flavonoids, Alkaloids, glycosides, steroids, phenol, saponins, and tannins. Pedalium murex L Aerosil, microcrystalline cellulose, cross povidone as a disintegrating agent, sodium starch glycolate, cross-linked sodium carmellose as a filler, and powdered Pedalium murex L mucilage as a binder were used to create the solid oral herbal dosage form, tablets. The angle of repose was found between 28.32 and 29.71, the range of bulk density was 0.47–0.49 mg/ml, and Density Tapped was 0.51–0.57 mg/ml was calculated. Hausner's ratio ranged from 1.15 to 1.29, and Carr's index was computed. The formulations' powder mixes showed good flow ability with Hausner's ratios of 1.2 or less. The powder blend's showed good flow ability was further demonstrated by the angle of repose, which is below 30 and ranges from 24 to 29. The research findings demonstrated the herbal tablet formulation potential preventing qualities against calcium oxalate crystal